FTA Research informs Resolution E/CN.9/2021/L.5 of the UN Commission on Population and Development - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA's presentation to the expert group informing the 54th session of the Commission on Population and Development which informed the resulting resolution E/CN.9/2021/L.5. The resolution calls for greater efforts to transform food systems emphasizing that promotion of agroecological practices is a key element for poverty eradication.